The tick plasma lectin, Dorin M, is a fibrinogen-related molecule - Rego, Ryan O; Kovář, Vojtěch; Kopáček, Petr; Weise, Christoph; Man, Petr; Šauman, Ivo; Grubhoffer, Libor (Insect biochemistry and molecular biology, 2006)
A lectin, named Dorin M, previously isolated and characterized from the hemolymph plasma of the soft tick, Ornithodoros moubata, was cloned and sequenced. The immunofluorescence using confocal microscopy revealed that Dorin M is produced in the tick hemocytes. A tryptic cleavage of Dorin M was performed and the resulting peptide fragments were sequenced by Edman degradation and/or mass spectrometry. Two of three internal peptide sequences displayed a significant similarity to the family of fibrinogen-related molecules. Degenerate primers were designed and used for PCR with hemocyte cDNA as a template. The sequence of the whole Dorin M cDNA was completed by the method of RACE. The tissue-specific expression investigated by RT-PCR revealed that Dorin M, in addition to hemocytes, is significantly expressed in salivary glands. The derived amino-acid sequence clearly shows that Dorin M has a fibrinogen-like domain, and exhibited the most significant similarity with tachylectins 5A and 5B from a horseshoe crab, Tachypleus tridentatus. In addition, other protein and binding characteristics suggest that Dorin M is closely related to tachylectins-5. Since these lectins have been reported to function as non-self recognizing molecules, we believe that Dorin M may play a similar role in an innate immunity of the tick and, possibly, also in pathogen transmission by this vector.
Keywords: financování organizované; Animals; Base Sequence; Hemocytes; slinné žlázy; Protein Structure, Tertiary; Salivary Glands; hemocyty; sekvence aminokyselin; Lectins; terciární struktura proteinů; Molecular Sequence Data; hmyzí proteiny; Amino Acid Sequence; lektiny; Financing, Organized; molekulární sekvence - údaje; Cloning, Molecular; Sequence Alignment; sekvence nukleotidů; Insect Proteins; klonování DNA; zvířata; Ornithodoros; sekvenční seřazení